Transforming Classroom Dynamics: The Impact of ChatGPT in English Speaking Class - Nehe, Berita Mambarasi; Setiawati, Eka; Rahman, Zainatul Shuhaida Abdull; Bastaman, Weny Widyawati; Purwantiningsih, Sri (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The integration of artificial intelligence (AI) tools in education has introduced transformative opportunities for improving teaching and learning practices. This study explores the impact of ChatGPT in university-level speaking classes, highlighting its positive impacts and challenges, an AI-powered language model, on classroom dynamics in English-speaking class. Employing a qualitative research which investigates how ChatGPT enhances students engagement, fosters collaborative interactions, and improves speaking proficiency among English as a Foreign Language (EFL) learners. The participants are students at a private University in Indonesia. Data were collected through classroom observations. The findings indicate that ChatGPT significantly boosting students confidence student through non-judgmental practice, providing consistent and personalized learning opportunities, offering immediate feedback, and exposing students to diverse communication scenarios. ChatGPT also supports vocabulary development and access to authentic materials. However, challenges remain, such as potential over-reliance on AI, limited social interaction, occasional inaccuracies, and technological barriers. Addressing these limitations is crucial for maximizing ChatGPT’s effectiveness in enhancing speaking skills. This study concludes that ChatGPT is a valuable resource for transforming classroom dynamics in English-speaking courses, promoting active participation, and enhancing speaking skills.